Faktor-faktor yang mempengaruhi ibu dalam memberikan imunisasi rutin lengkap di wilayah kerja Puskesmas Inuman - Rendi Randika; Suci Amin; Optimis Sriwati (Pelantar Press, 2021)
Infant and toddler mortality rates due to diseases that can be prevented by immunization still show quite high rates. Basic immunization serves to protect and reduce the risk of morbidity and mortality from diseases that can be prevented by immunization. The purpose of this study was to determine the factors that influence mothers in providing routine routine immunizations in the work area of Inuman Health Center. This type of research is observational analytic with the